QRIS (QUICK RESPONSE INDONESIAN STANDARD) SEBAGAI STANDAR PEMBAYARAN NON TUNAI DI INDONESIA - Feby Cantika Sari (2021)
The rapid pace of technological development coupled with the Covid-19 pandemic that hit Indonesia since last year has changed the pattern of payment transactions used by Indonesians. Payment methods through e-wallets and QR Codes are getting popular because of their speed in transaction settlement. In anticipation the growth of QR Code payment industry, Bank Indonesia together with the Indonesian Payment System Association issued a cashless payment standard called Quick Response Indonesian Standard (QRIS). This paper aims to know the standardization of noncash payments in Indonesia with QRIS, the implementation of socialization of QRIS, QRIS development opportunities and the existence of QRIS in Indonesia. The results showed that QRIS became the national standard in QR Code payment transactions for an efficient, fast, reliable and secure retail payment system. Education and socialization has been conducted throughout Indonesia and almost 7 million merchants have used QRIS, indicating huge development opportunities. There are several challenges that must be faced to achieve a solid QRIS existence in Indonesia, such as low digital financial literacy and low internet access rates. These challenges can be overcome if the government and all levels of society work together to optimize education and infrastructure development as needed.